PENGEMBANGAN PRODUK, KONSEP DAN PROSES MANUFAKTURING GUNA MENINGKATKAN EFISIENSI DAN EFEKTIFITAS - Endro Prihastono (Jurnal Ilmiah Dinamika Teknik, 2010)
The analysis of product and manufacturing process is the initiate activity and become a base in planning an industrial activity. The error in the early analysis will cause a fatal effect in the following process. Product analysis is an activity which will change the last product into the components of the product former in detail: specification, volume, and the amount of the product. Meanwhile process analysis is plan of a step which is needed to make another product from the early to the end of the process. Keyword: Analysis Product, Manufacturing Process